2013
DOI: 10.1590/s1806-37132013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison between the mycobacteria growth indicator tube system and Löwenstein-Jensen medium in the routine detection of Mycobacterium tuberculosis at public health care facilities in Rio de Janeiro, Brazil: preliminary results of a pragmatic clinical trial

Abstract: In view of the fact that the World Health Organization has recommended the use of the mycobacteria growth indicator tube (MGIT) 960 system for the diagnosis of tuberculosis and that there is as yet no evidence regarding the clinical impact of its use in health care systems, we conducted a pragmatic clinical trial to evaluate the clinical performance and cost-effectiveness of the use of MGIT 960 at two health care facilities in the city of Rio de Janeiro, Brazil, where the incidence of tuberculosis is high. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
1
2
0
3
Order By: Relevance
“…This result is consistent with previous studies of MGIT 960 in Brazil and other countries (12) (13) . MGIT 320 and MGIT 960 require the same sample processing, as well as the same additional tests to confi rm infection with M. tuberculosis.…”
Section: Conflict Of Interest Financial Support Referencessupporting
confidence: 94%
See 1 more Smart Citation
“…This result is consistent with previous studies of MGIT 960 in Brazil and other countries (12) (13) . MGIT 320 and MGIT 960 require the same sample processing, as well as the same additional tests to confi rm infection with M. tuberculosis.…”
Section: Conflict Of Interest Financial Support Referencessupporting
confidence: 94%
“…Accordingly, we found that Ogawa-Kudoh and MGIT cultures accounted for 51% and 60% of positive diagnoses. respectively, as assessed by published methods (12) (13) (14) . Notably, the kappa index was 0.9 between Ogawa-Kudoh and MGIT cultures, indicating excellent agreement (p < 0.0001).…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 99%
“…Em quatro (24%) dos artigos, foi explicitada a necessidade de uma amostra populacional maior, sendo que, entre esses, um ressaltou viés populacional por gênero, uma vez que 84% dos participantes eram mulheres; em dois outros artigos, haveria a necessidade de uma diversidade maior entre os participantes da amostra (em um deles, a amostra continha apenas estudantes universitários e na outra, os participantes eram estudantes de uma escola de acupuntura). No entanto, é o design de escolha determinar a relação custo-benefício (Moreira et al, 2013;Huf & Kritski, 2012).…”
Section: Discussionunclassified
“…Apesar de se considerar que os estudos pragmáticos não fornecem informações conclusivas sobre a especificidade do efeito de determinados tratamento, podemos observar algumas características interessantes: (a) o desenho de um estudo pragmático reflete variações entre pacientes que ocorrem na prática clínica real e não em circunstâncias clínicas reais artificiais, aproximando a pesquisa científica da complexidade do contexto clínico (Roland & Torgerson, 1998;Ware & Hamel, 2011;Huf & Kritski, 2012); (b) são mais aderentes à prática convencional do tratamento sob investigação (Ware & Hamel, 2011;Moreira et al, 2013); (c) geralmente são mais simples e mais baratos do que ensaios explicativos (Moreira et al, 2013;Huf & Kritski, 2012); (d) respondem diretamente à pergunta (fundamental para o profissional da saúde): ''devo propor este tratamento para um paciente pela condição X (Roland & Torgerson, 1998;MacPherson, 2004;Huf & Kritski, 2012)"; (e) avaliam a efetividade de um tratamento, ao invés de sua eficácia (Coutinho & Bloch, 2003;Huf & Kritski, 2012); (f) podem incorporar uma população heterogênea de pacientes; (g) os regimes de tratamento tendem a ser mais flexíveis, acomodando assim as necessidades individuais dos pacientes (Coutinho & Bloch, 2003).…”
Section: Introductionunclassified
“…Conversely, it would be prudent to continue using the solid medium for the specimens most difficult to obtain, such as biopsy specimens, where only a single sample is typically available. The higher rates of contamination in MGIT medium demonstrated in some studies (5,6,7,8) and the isolation of a greater number of NTM of unclear clinical significance found in liquid medium (7) would preclude isolation of the mycobacterial pathogen in unique extrapulmonary samples if cultures were done only on MGIT medium.Decisions about laboratory utilization need to be made in the context of the local epidemiology, with the cost of extra testing weighed against the additional yield obtained. We submit that such decisions need to extend beyond laboratory isolation to case detection.…”
mentioning
confidence: 99%